Plants discovered in Costa Rica between 2010 and 2020 and their possible pharmacological use - Vargas Zúñiga, Rolando (2025)
Costa Rica is known for having 6% of the world's biodiversity, approximately 12% of the plant species that exist in the country are endemic and because in Costa Rica the use of plants for medicinal purposes has been a tradition, it is important to know the potential pharmacological activities of the species that have recently been discovered. A bibliographic search was carried out under the criteria: Costa Rican species, endemic, recently discovered (2010-2020), that have few studies, that present ethnobotanical uses or that the family to which they belong, report this type of medicinal use. One or more criteria had to be met and, therefore, information on plants from 18 families is reported. Finally, it is very important to carry out more research on the large number of plant species that have been discovered in Costa Rica since it could be useful to know the molecular and phytochemical profile of these species both to know if they have pharmacological potential, as well as to know better its taxonomic and evolutionary classification.